Influence of remaining coronal thickness and height on biomechanical behavior of endodontically treated teeth: survival rates, load to fracture and finite element analysis - Gislene Corrêa; Lucas P Brondani; Vinícius F. Wandscher; Gabriel K. R. Pereira; Luiz F. Valandro; César D. Bergoli (University of São Paulo, 2018)
Abstract Objective To evaluate the effect of restorative strategy (fiber post vs cast post and core), coronal height (0 mm vs 2 mm) and thickness (higher than 1 mm vs lower than 1 mm) on survival rate, fracture resistance and stress distribution. Material and Methods Seventy-two bovine teeth were cleaned and allocated in six groups (n = 12). Twenty-four teeth were sectioned at 13 mm length (no remaining coronal structure) and forty-eight were sectioned at 15 mm (2 mm remaining coronal structure). Half of the forty-eight had remaining coronal thickness lower than 1 mm and the other half had thickness higher than 1 mm. All root canals were prepared at 10 mm (luting length), fiber posts were cemented in thirty-six specimens and cast post and core in other thirty-six. All teeth were restored with metallic crowns. Specimens were submitted to 1.5 million cycles (100 N, 45°, 10 Hz at 2 mm below incisal edge) and evaluated at each 500,000 cycles to detect failures. Specimens that survived were submitted to load to fracture test. Bidimensional (Rhinoceros® 4.0) models were obteined survival data submitted to Kaplan-Meier (α=0.05) analysis and load to fracture values submitted to ANOVA and Tukey tests (α=0.05). Results Groups without remaining coronal structure showed survival rates lower than other groups (p=0.001). ANOVA showed higher values of load to fracture for groups with coronal thickness higher than 1 mm (p=0.0043). Finite element analysis showed better stress distribution in groups with remaining coronal structure and restored with fiber post. Conclusion Specimens without remaining coronal structure have lower survival rates. Specimens with remaining structure lower than 1 mm and without coronal structure support the same load to fracture value independently of the restorative strategy.